Localized Sustainable Development Goals Changes and Their Response to Ecosystem Services—A Case of Typical Southern Hilly Regions in China - Chang You; Shidong Zhang; Wenshu Liu; Luo Guo (Land, 2024)
Sustainability has become an indispensable core consideration when nations formulate their development policies. This study delves into the dynamic correlations between ecosystem services (ESs) and localized Sustainable Development Goals (SDGs) in a typical hilly region in southern China. Various ESs were computed using the InVEST model, while spatial econometric models were employed to assess ES responses to SDG targets at the county, sectoral, and overall spatial levels. The findings revealed the following. (1) From 2005 to 2020, there were differences in the development rates of various SDG targets in Ganzhou. Except for SDG 15, which declined, the development of the other targets showed an overall increasing trend. The development of the various SDG targets was relatively balanced, but SDG 9 and SDG 7 had the highest growth rates, ranging from 9.4% to 10.7% and 9.4% to 10.3%, respectively. The comprehensive SDG assessment index exhibited significant spatiotemporal variation, with a general trend of higher values in the north and lower values in the south. (2) The local ES showed a delayed response to SDG 1 and SDG 2, but there was a significant positive response to SDG 3, SDG 4, SDG 6, SDG 8, and SDG 9. However, responses to SDG 7, SDG 11, SDG 13, and SDG 15 showed regional differences. This study not only provides valuable insights for sustainable development in Ganzhou and other regions of China but also offers Chinese perspectives and experiences that may inform global efforts towards SDG implementation. This study fills the gap in existing research by constructing a localized SDG indicator system and quantifying each SDG indicator, further exploring the response of the ES to each SDG in the region. Looking ahead, we anticipate further research to deepen the understanding of the relationship between ESs and SDG targets on a broader geographical scale and over longer timeframes, aiming to provide a more robust scientific foundation for building a harmonious coexistence between humans and nature in the future.